Analysis of the Temporal and Spatial Evolution of Carbon Storage in the Yarlung Zangbo River Basin Based on the InVEST Model - Ma Yujie; Zhou Boyi; Yu Jinyuan (E3S Web of Conferences)
In this research, InVEST and PLUS are combined to analyse the spatial and spatial distribution of carbon stock in the Yarlung Zangbo River Basin. The results show that (1) Yarlung ZangboRiver Basin is predominantly wooded and grassland, which makes up over 67% of the watershed’s overall surface. Between 2015 and 2020, the number of plots devoted to buildings and unutilised land increased, whereas the number of other land types decreased. The shift in land-use was concentrated primarily on forestry, pasture and unused land. (2) Between 2015 and 2020, YarlungZangbo River Basin experienced a first fall and then a rise, leading to a total loss of about 0.84×106 tons. Most of the carbon deposits are concentrated in the middle and lower latitudes of the Basin.